The influence of structural arrangement on long-duration blast response of annealed glazing. (15th October 2016) - Johns, Robert V.; Clubley, Simon K.
Highlights: Glazing fragmentation and inferred hazard is a strong function of edge conditions. Rigid supports produce greater cracking and smaller fragments than elastic edges. Breakage threshold proximity dictates effect of structural arrangement on response. Edge supports and aspect ratio varies break time by up to ∼30% in high-power blast. AEM able to computationally model glazing deflection and fracture mode. Abstract: This paper investigates the influence of structural arrangement on long-duration blast loaded annealed glazing via variable thickness, area, aspect ratio and edge support conditions. Initially, the findings of eighteen full-scale air-blast trials employing 33 annealed glazing panels are reported where it is demonstrated that fracture mode and fragmentation are a strong function of edge supports. Rigidly clamped edges are shown to induce localised stress transmission, producing significant cracking and small fragments. In contrast, elastic edges are shown to produce large, angular fragments, demonstrating the importance of accurately modelling edge conditions when analysing fragment hazard. Quantification of peak centre panel deflection and breakage time is then presented where variable results indicate the influence of edge supports and aspect ratio to be dependent on proximity to the threshold area as a function of glazing thickness. An initial Applied Element Method (AEM) analysis is then employed to model the influence of structural arrangement on long-duration blast-loaded annealed glazing. AEM models are shown to reasonably predict glazing fragmentation behaviour, breakage time and peak panel deflection at the moment of breakage. Thus indicating AEM's potential suitability to provide a predictive capacity for annealed glazing response during long-duration blast.